Istinbāṭh Hukum Dan Etika Penciptaan Dalam Film Frankenstein (2025): Analisis Ushul Fiqh Terhadap Fenomena Sains Kontemporer - Rizal Nazarudin Firdaus; Muhamad Fuad Ramadhan; Yanwar Faturrahman; Tenny Sudjatnika (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyse the issue of creation ethics in the film Frankenstein (2025) from the perspective of Islamic legal theory (Uṣūl al-Fiqh), particularly through the process of istinbāṭ al-ḥukm in addressing contemporary legal problems (al-nawāzil). The film portrays the creation of artificial life driven by scientific ambition while neglecting ethical considerations and moral responsibility. This research employs a qualitative approach using content analysis to examine key scenes and dialogues related to the act of creation, the creator–creature relationship, and the resulting social consequences. The analysis is conducted through the framework of maqāṣid al-sharī‘ah, including the principles of ḥifẓ al-nafs (protection of life), ḥifẓ al-‘aql (protection of intellect), ḥifẓ al-‘ird (protection of human dignity), sadd al-dharī‘ah (blocking the means to harm), ma’ālāt al-af‘āl (consideration of consequences), and al-ḍarar yuzāl (harm must be eliminated). The findings indicate that the act of creation depicted in Frankenstein (2025) cannot be normatively justified within Islamic law, as it fails to uphold public welfare, disregards the consequences of actions, and results in harm and social inequality. This study highlights the methodological relevance of Uṣūl al-Fiqh in addressing ethical challenges posed by modern science and technology, emphasizing the necessity of integrating scientific advancement with ethical responsibility and the objectives of Islamic law.